Partycypacja pracowników jako metoda ewolucyjnego przygotowania pracowników do rewolucyjnych zmian - Stankiewicz, Janina; Moczulska, Marta (The employee participation as method of evolutionary the workers' preparation to revolutionary changes, 2006)
Considering, that in present organizations often and often revolutionary changes is essential, meaning of execution of working participation was shown. Attention was concentrated on direct, voluntary and active participation. Forming of proper relations between employees and managers for applying of so implied and effective participation is evolutionary process.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 661-667